EVALUATION OF HYDROCARBON DEW POINT (HCDP) AND GAS COMPOSITION FORECASTING USING TIME SERIES ANALYSIS - Putra Tri Aditya Nugraha, Maha
Natural gas is made up of a mixture of components that vary widely. The largest component of natural gas is methane, a compound with one carbon atom and four hydrogen atom (CH4). The different sources will give a unique contribution to complete the natural gas properties of the field. Therefore, the natural gas of each field will be different from another field. The unique properties will form a new term in gas delivery, namely the quality of natural gas. Natural gas quality is determined by the relative quantities of the properties, therefore also varies considerably. Natural gas quality is considered to have several specifications to be used in the inspection phase before the gas being exported. Under these conditions, operators shall have the capability to ensure that all operation to work optimally in accordance with the requirements specified in the contract. In addition, the energy carried by the gas will also be reduced if the gas is delivered outside of the specified requirements. Hydrocarbon Dew Point (HCDP) Temperature would be one of many specifications that will affect the gas quality. Hydrocarbon Dew Point (HCDP) Temperature is determined by the quantities of each component of the gas. Based on the contract, Hydrocarbon Dew Point (HCDP) Temperature must be less than 55 °F in the delivery point. One of the world’s longest subsea gas pipeline, called X pipeline, has some challenges with the gas quality issues. The X pipeline delivers dry gas from different suppliers. Under the contract, the suppliers of the X pipeline have to place orders for the gas a day until a week ahead of the supply delivered. Because of that, the engineers need a tool that can be used for monitoring of gas quality, Hydrocarbon Dew Point (HCDP) Temperature, from all suppliers to meet the specified contract. This study leads to the prediction of Hydrocarbon Dew Point (HCDP) Temperature in time in the future by using time series analysis. Time series analysis is used to understand the behavior of the composition data in the range of a certain time and will predict the future. The output of this method is in the form of a predicted composition. This future composition will be used as input data to calculate the Hydrocarbon Dew Point (HCDP) Temperature by numerical approaching (using Python program). After all, Time series analysis methods have solved to predict the Hydrocarbon Dew Point (HCDP) Temperature in each supplier of X pipeline. The result of this study shows that the obtain error is less than 3% and the calculated Hydrocarbon Dew Point (HCDP) Temperature in a week ahead still in the specified requirements in the contract. This study also presents a comparison between the results of commercial software and calculated result.